Validation of dietary assessment methods for PFOS exposure using biomonitoring data in a senior population with metabolic syndrome - Nadine Khoury; Nancy Babio; María Ángeles Martínez; Eleni Serafeim; Danae Costopoulou; Lucía Iglesias-Vazquez; Leondios Leondiadis; Jordi Salas-Salvadó (Environment International)
Perfluorooctanesulfonic acid (PFOS) exposure through diet represents an escalating public health concern due to its bioaccumulation and potential adverse health effects. This study aimed to validate the assessment of dietary PFOS intake by examining the relationship between estimated dietary intake and plasma PFOS concentrations in 196 participants with overweight or obesity and metabolic syndrome from Spain. PFOS dietary intake was assessed using validated food frequency questionnaires (FFQs) and using EFSA’s updated PFOS food concentration data. Plasma PFOS levels were measured using Ultra-High-Performance Liquid Chromatography and Mass Spectrometry in Tandem (UHPLC-ESI-MS/MS). Statistical analyses included Spearman correlation, independent t-tests, Kappa agreement, and partial regression models, all adjusted for demographic and lifestyle variables. The results demonstrated a statistically significant correlation and a fair agreement between estimated dietary PFOS intake and plasma PFOS concentrations, supporting the modest reliability of FFQs for estimating dietary exposure. While these findings suggest that FFQs could provide a practical, non-invasive approach for dietary PFOS exposure assessment, the fair agreement observed in Kappa analysis indicates that FFQs alone may not fully capture individual exposure levels. Future research should focus on refining dietary exposure assessment tools, improving validation methods to enhance the accuracy of PFOS exposure estimates in epidemiological studies.